Investigating the performance of cycling and hockey helmet liner materials in mitigating impacts at lower speeds during free falls - Hegde, S.; Liu, M.; Zerpa, C. (ISBS Proceedings Archive (Michigan), 2023)
This study examined the performance of helmets made of expanded polystyrene (EPS) and expanded propylene (EPP) in mitigating linear impacts over three consecutive drop trials at 16 impact speeds ranging from 0.93 to 3.96 m/s. It was found that EPS, a liner material used in cycling helmets, had lower capacity of mitigating linear impact acceleration and captured a larger compressed area of impact than the EPPs, liner materials used for hockey helmets. EPS and EPPs all experienced some degrees of loss in their capacities to mitigate acceleration after the initial impact. All tested materials had no statistically significant difference in their peak resultant linear acceleration (PRLA) between the first and third impacts, and the second and third impacts. This study also found strong and positive correlations between ellipse area and PRLA.